Heroes of Berrien County: World War 2 Scrapbook, Volume 1 - Berrien Historical Foundation (My University, 1932)
This item is a collection of newspaper clippings detailing the events of Berrien County between 1932 and 1949. Reoccurring themes are soldiers being called up for service in the armed forces and the stories that are sent home. In addition to regular news stories from the region around the same time. Other items like certificates and photos are included.
This item contains 1 PDF with a title page and 49 PNG files
Keywords: World War 2; Newspaper; Historic preservation--Georgia--Berrien County; Berrien County Historical Foundation (Nashville; Ga.); Berrien County (Ga.); Electronic records